2019
DOI: 10.3390/ijms20092156
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Folate-Mediated Liposomal Encapsulated Arsenic Trioxide for Treating HPV-Positive Cervical Cancer Cells In Vitro

Abstract: High-risk human papilloma virus (HPV) infection is directly associated with cervical cancer development. Arsenic trioxide (ATO), despite inducing apoptosis in HPV-infected cervical cancer cells in vitro, has been compromised by toxicity and poor pharmacokinetics in clinical trials. Therefore, to improve ATO’s therapeutic profile for HPV-related cancers, this study aims to explore the effects of length of ligand spacers of folate-targeted liposomes on the efficiency of ATO delivery to HPV-infected cells. Fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…The system was constructed by loading ATO into the cavity of the spheres and coupling microwave (MWA)-sensitive intelligent switch and the targeting molecule on the surface to structure the system of TPP-PCM-ATO@ZrO 2 (abbreviated as TPA@ZrO 2 ). The drug loading efficiency was improved to 54.5% compared with the 25% of liposome in the previous study . Through a series of in vitro and in vivo experiments using the HepG2 cell line and a mouse H22 subcutaneous tumor model, we demonstrated that ATO could be accurately released in a controlled manner in targeted lesions and accumulated to a lethal dose.…”
Section: Introductionmentioning
confidence: 69%
“…The system was constructed by loading ATO into the cavity of the spheres and coupling microwave (MWA)-sensitive intelligent switch and the targeting molecule on the surface to structure the system of TPP-PCM-ATO@ZrO 2 (abbreviated as TPA@ZrO 2 ). The drug loading efficiency was improved to 54.5% compared with the 25% of liposome in the previous study . Through a series of in vitro and in vivo experiments using the HepG2 cell line and a mouse H22 subcutaneous tumor model, we demonstrated that ATO could be accurately released in a controlled manner in targeted lesions and accumulated to a lethal dose.…”
Section: Introductionmentioning
confidence: 69%
“…The concentration of ions (Zn(II), Cu(II), Ni(II), Co(II), Mn(II)) in purified TOPs proteins was determined using an inductively coupled plasma–mass spectrophotometer (ICP-MS) (PerkinElmer SCIEX, ELAN DRC II), which has a limit of quantification of 1 μg/L, as described in ( 91 , 92 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cervical cancer is a common malignant tumor of the female reproductive system with a high incidence [ 64 ]. There are 500,000 new cases annually in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Akhtar utilized ICP-OES for the quantitative analysis of arsenic. Figure 7 G, H show that neutral liposomes of 100 nm were the highest drug loading rate, which was 24.2%As/P (± 0.848) [ 64 ]. In addition, the cytotoxicity test showed that neutral liposomes were the least toxic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation